Andrographolide promotes proliferative and osteogenic potentials of human placenta-derived mesenchymal stem cells through the activation of Wnt/β-catenin signaling - Naruphong Phunikom (2022)
Introduction: The in vitro expansion and differentiation of mesenchymal stem cells derived from bone marrow (BM-hMSCs) are considered as potential therapeutic tools for clinical applications in bone tissue engineering and regenerative medicine. However, invasive sampling and reduction in number and proliferative capacity with age are the major limitations of BM-hMSCs. Recently, human placenta-derived MSCs (PL-hMSCs) obtained by a non-invasive procedure have attracted much interest. Attempts to increase the potential of PL-hMSCs would be an important paradigm in regenerative medicine. Herein, we examined the proliferative and osteogenic effect of andrographolide (AP) on PL-hMSCs. Methods: Mesenchymal stem cells were isolated from full-term normal human placentas and were characterized before using. Cell cytotoxicity and proliferative effect of AP were examined by MTT and BrdU assay, respectively. The non-toxicity concentrations of AP were further assessed for osteogenic effect determined by alkaline phosphatase (ALP) expression and activity, alizarin red staining, and osteoblast-specific gene expressions. Screening of genes involved in osteogenic differentiation-related pathways modulated by AP was explored by a NanoString nCounter analysis. Results: PL-hMSCs generated in this study met the MSC criteria set by the International Society of Cellular Therapy. The non-cytotoxic concentrations of AP on PL-hMSCs are up to 10 μM. The compound increased PL-hMSC proliferation concomitant with increases in Wnt/β-catenin level and activity. It also enhanced osteogenic differentiation in association with osteoblast-specific mRNA expression. Further, AP promoted bone formation and increased bone structural protein level, osteocalcin, in osteoblastic cells. Gene screening analysis showed the upregulation of genes related to Wnt/β-catenin, TGFβ/BMP, SMAD, and FGF signaling pathways. Conclusion: We demonstrated, for the first time, the potential role of AP in promoting proliferation, osteogenic differentiation, and osteoblast bone formation of PL-hMSCs. This study suggests that AP may be an effective novel agent for the improvement of PL-hMSCs and stem cell-based therapy for bone regeneration.